The effectiveness of drama and communicative approach in the teaching of subject-verb agreement to primary five pupils of SK. St. Patrick Semadang / Allen Moha - Moha, Allen (2007)
The purpose of this research study is to investigate the effectiveness of using a combination of drama and communicative approach to teach subject-verb agreement to twenty-two Primary Five pupils of SK. St. Patrick Semadang, Kuching. The researcher employed Pre-Test, Post-Test, and Observation techniques to collect the data for this study. A comparative analysis of the data gathered from the Pre-Test and Post-Test revealed that the results of the findings support the research hypotheses. Thus, the researcher arrived at the conclusion that using a combination of drama and communicative approach to teach subject-verb agreement is effective as illustrated by the significant increase of 17.64% in pupils’ performance. The study concludes that the significance increases in the performances is indicative of the pupils having shown interactive responses and are motivated to learn via drama and communicative approach.